Removal of despotic political regime: the Abū Dharr’s legacy and its legitimacy - Jani, Mohd. Shah; Fatah Yasin, Raudlotul Firdaus (IIUM Press, International Islamic University Malaysia, 2020)
This article is a humble attempt at highlighting the controversies regarding the legitimacy of popular resistance or revolutionary movement to bring down Muslim political regime that claimed to be despotic, unjust and even un-Islamic. Having the fact on the existence of another view by majority scholars that more inclined towards pacifist ideology which stressed on political stability as a prerequisite to prosperity, the article emphasizes more on the revolutionary school, while the second shall be highlighted when it is necessary for comparison. Employing qualitative method of study, the article seeks to examine the arguments provided by both movements. This will be done by analyzing their textual and rational grounds of evidences used by the two schools to legitimize their political stance. Associating with what is happening in Muslims nation nowadays, current study compelled to review the radical revolutionary movement from the perspective of moderate Islam school of thought.